2008
DOI: 10.1371/journal.pone.0003118
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Limits Peripheral Lymphocyte Numbers through T Cell Homeostatic Mechanisms

Abstract: BackgroundIL-21, a member of the common γ-chain utilizing family of cytokines, participates in immune and inflammatory processes. In addition, the cytokine has been linked to autoimmunity in humans and rodents.Methodology/Principal FindingsTo investigate the mechanism whereby IL-21 affects the immune system, we investigated its role in T cell homeostasis and autoimmunity in both non-autoimmune C57BL/6 and autoimmune NOD mice. Our data indicate that IL-21R knockout C57BL/6 and NOD mice show increased size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 64 publications
5
57
2
1
Order By: Relevance
“…IL-21 is necessary for the development of diabetes in the NOD mouse (23)(24)(25), but a number of important studies argue that decreased expression of IL-2 explains Idd3 (14,15,31). Our findings resonate with a critical role for IL-21 in T1D pathogenesis, but do not formally discount a role for IL-2.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…IL-21 is necessary for the development of diabetes in the NOD mouse (23)(24)(25), but a number of important studies argue that decreased expression of IL-2 explains Idd3 (14,15,31). Our findings resonate with a critical role for IL-21 in T1D pathogenesis, but do not formally discount a role for IL-2.…”
Section: Discussioncontrasting
confidence: 55%
“…IL-21 is produced by activated CD4 ϩ T cells and NK T cells, and can deliver a costimulatory signal to lymphocytes that affects their proliferation, differentiation, and survival in response to antigen (19)(20)(21). Consistent with its actions on lymphocyte populations, IL-21 has been shown to have an essential role in an array of conditions involving the destruction of self-tissues (20,(22)(23)(24). We have previously shown that NOD mice exhibited elevated levels of IL-21 (26), and a number of recent studies of NOD mice made genetically deficient in the IL-21R demonstrate that IL-21 is necessary for the development of T1D (23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans several autoimmune diseases including type 1 diabetes, rheumatoid arthritis and Crohns have been associated with lymphopenia 42,43 . Moreover, mild lymphopenia and compensatory IL-21-dependent homoeostatic proliferation in nonobese diabetic mice that are prone to the development of autoimmunity have been reported to promote type 1 diabetes 44,45 . Similarly, deregulated regulatory T-cell expansion in lymphopenic nonobese diabetic hosts contributes to the development of type 1 diabetes 46 , whereas IL-7-mediated T-cell LIP in lupus or type 1 diabetes predisposed mice enhances their progression to disease 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of autoimmune colitis, IL-6-dependent spontaneous proliferation of colitogenic CD8 + T cells and their conversion to IL-17-producing effector cells underlie the pathogenic process (7). In the NOD mouse model, genetic ablation of IL21Ra abrogated the development of autoimmune diabetes (8)(9)(10). In a mouse model of autoimmune diabetes, IL-7 promoted the activation of autoreactive CD8 T cells by facilitating CD4 T cells to provide help (11).…”
mentioning
confidence: 99%